Pengembangan Gim Simulasi Jalur Evakuasi Bencana Kebakaran di Kampus Menggunakan Metode ADDIE - Julius Bata; Laura Imanuelle Defira (STMIK Budi Darma, 2023)
Fire disasters frequently occur, resulting in both material and human losses. One of the places at risk of a fire disaster is the campus building. The campus is the center for academic activities involving faculty, students, staff, and visitors. This situation makes the campus a densely populated area susceptible to human casualties in a fire. In such emergencies, knowledge of evacuation routes is crucial for human safety. However, many academic members, especially students, need more information about evacuation routes. This research aims to develop a simulation game for socializing evacuation routes within the campus III building of Universitas Katolik Indonesia Atma Jaya BSD. We employ The ADDIE (Analysis-Design-Development-Implement-Evaluation) method to develop the game. The analysis stage is carried out by analyzing information about evacuation routes. Based on the results of the analysis, the design stage was carried out to design the game flow and quest in the game. After that, development, which consists of asset and game development, is carried out. The game assets, including a three-dimensional model of the building and attributes, are created using Blender. These assets are then integrated with the game logic using the Unity game engine. Evaluation is conducted by safety experts at Unika Atma Jaya and through black-box testing. The black-box testing results indicate that all game functions perform well. Experts opine that the game application can serve as a medium for socializing evacuation routes. Future research will focus on user testing by students.